Ending the US embargo of Cuba: international law in dispute - White, Nigel D. (Cambridge University Press, 2018)
The announcement by Presidents Obama and Castro in December 2014 of a major step towards normalisation of inter-state relations was part of what is primarily a political process, but normalisation implies a return to peaceful inter-state relations based on respect for fundamental principles of international law. This commentary explores the role that those principles have played in helping shape the confrontation between the United States and Cuba since the revolution of 1959, which has been underpinned by an economic, commercial and financial embargo of Cuba by the United States. From being an integral part of the bilateral dispute, this commentary argues that at key moments international law can shift to form part of a solution. The changing political landscape raises the prospects of the parties turning to international law as a means of restoring normal relations between the two countries resulting, amongst other changes, in the demise of the embargo.